Mechanical Properties of Goat Hoof Fiber Reinforced Polystrene Composite for Car Bumper - Nathan, C.; Bwala, E. B.; Barnabas, A. A.; Ayomikun, I. Y. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Natural materials are good reinforcements for composite materials due to their eco-friendliness and potentials for improved mechanical properties. This study explores the potential of goat hoof fibers as a reinforcing material in polystyrene composites for car bumpers. Different % composition mixes of goat hoof fibers and polystyrene matrix were used as samples A-F. Samples A(100% polystyrene and 0% goat hoof), sample B(90% polystyrene and 10% goat hoof), sample C(80% polystyrene and 20% goat hoof), sample D (70% polystyrene and 30% goat hoof), sample E (60 polystyrene and 40% goat hoof), sample F (50 polystyrene and 50% goat hoof. The samples were then moulded into different shapes depending on the type of test to be conducted on the samples. The test conducted on sample composition mixes are tensile test, impact test, flexural test and hardness The results of the experiments conducted on sample D (70% polystyrene and 30% goat hoof) gave the following results (14.9MPa, 75.23KN, 71.3MPa, 56.92KN/m2) and for sample E (60% polystyrene and 40% goat hoof) gave the following results (11.66MPa, 69.2KN, 71.2MPa, 51.4KN/m2) and for sample C (80% polystyrene and 20% goat hoof) gave the following results (10MPa, 70.9KN, 70.9MPa, 46.2KN/m2) respectively. The results of the values obtained by samples D, E and C composition mixes gave values that compare reasonable with the values obtained by the conventional car bumpers.